Brand culture: its antecedents and relationship to SME brand performance - Gisip, Imelda Albert; Harun, Amran (Iwnest Publisher, 2015)
The study develops and empirically tests a model of the antecedents of brand culture and its effects of on brand performance in Malaysian small and medium-sized enterprises (SMEs). Objective: In this study, three research questions are addressed: (1) What effects do organizational internal factors (i.e. corporate supportive resources and market orientation) have on brand culture? (2) What effect does brand culture has on brand performance? (3) To what extent brand culture mediate relationship between organizational internal factors and brand performance? Results: Findings confirm the validity of the model. It also indicates brand culture, appears to be a key mediator in the web of relationships among organizational internal factors and brand performance.